Kesalehan dan Ketekunan Ayub Kepada Allah dalam Penderitaan-Nya - Yohanes Yappo; Callista Anugrahni; Tirza Tanzania; Sarmauli Sarmauli (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
The purpose of writing this article is to identify and know the life story of the character of Job. The character of Job is a person who has a righteous personality, is honest, fears God, and shuns evil. The story begins with a portrayal of a man who is very pious, blessed and wealthy, then continues with a severe test that changes his life.